2017
DOI: 10.1038/ncomms15466
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation syndrome-associated genetic variants affect transcription factor binding and alternative splicing of LOXL1

Abstract: Although lysyl oxidase-like 1 (LOXL1) is known as the principal genetic risk factor for pseudoexfoliation (PEX) syndrome, a major cause of glaucoma and cardiovascular complications, no functional variants have been identified to date. Here, we conduct a genome-wide association scan on 771 German PEX patients and 1,350 controls, followed by independent testing of associated variants in Italian and Japanese data sets. We focus on a 3.5-kb four-component polymorphic locus positioned spanning introns 1 and 2 of LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 67 publications
(95 reference statements)
1
68
0
6
Order By: Relevance
“…39 On the other hand, LOXL1 expression was found to be significantly downregulated below homeostatic levels in elastin-rich intraand extraocular connective tissues, such as the lamina cribrosa and aortic wall. 19,26 Reduced LOXL1 expression levels were found to be associated with pronounced elastotic and biomechanical alterations, which have been suggested to predispose to the development of glaucoma and cardiovascular FIGURE 2. Effects of NMD suppression on expression levels of LOXL1 and LOXL1-a.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…39 On the other hand, LOXL1 expression was found to be significantly downregulated below homeostatic levels in elastin-rich intraand extraocular connective tissues, such as the lamina cribrosa and aortic wall. 19,26 Reduced LOXL1 expression levels were found to be associated with pronounced elastotic and biomechanical alterations, which have been suggested to predispose to the development of glaucoma and cardiovascular FIGURE 2. Effects of NMD suppression on expression levels of LOXL1 and LOXL1-a.…”
Section: Discussionmentioning
confidence: 99%
“…24 All hTCF were homozygous for the risk alleles of the two coding SNPs, rs1048661T>G and rs3825942A>G, as well as the four intronic SNPs, rs12905253G>A, r s11638944C>G, rs12441130T>C, rs11631579A>G, which had been previously shown to influence alternative splicing of LOXL1. 26 Primary human optic nerve head astrocyte (hONHA) cultures were generated from lamina cribrosa tissue of five healthy donor eyes (74 6 9 years) with appropriate research content as previously described. 19 Primary human trabecular meshwork cells (hTMC) were obtained from Provitro (Berlin, Germany) and grown in Dulbecco's modified Eagle's medium (DMEM; Pan Biotech, Aidenbach, Germany) supplemented with 10% fetal bovine serum (FBS; Pan Biotech) and 1% antibiotic (penicillin/streptomycin/amphotericin B; Pan Biotech).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the risk sequence had an increased activity at the transcriptional level that was associated with decreased binding affinity of transcription factor (RXR α ) and enhanced differential splicing of LOXL1 pre‐mRNA along with nonsense‐mediated mRNA decay (Pasutto et al. ). Differential splicing coupled to nonsense‐mediated mRNA decay was later shown to regulate expression of LOXL1 at the post‐transcriptional level in response to XFS‐associated environmental and nutritional factors (Berner et al.…”
Section: Genetic Factors: Loxl1mentioning
confidence: 99%